Managing major data of genetically modified mice: from scientific demands to legal obligations - Staudt, Michael; Sitek, Dagmar; Schenkel, Johannes (Transgenic research, 2012)
The number of genetically modified mice is increasing rapidly. Several limitations when working with these animals are to be considered: small colonies, the continued danger of loss, often a limited breeding-success, the need to keep those mutants in stock, difficult and costly import-procedures, and also a major (scientific) value of those mutants often available only with major restrictions. To gather relevant information about all active and archived genetically modified mouse lines available in-house (>1.500) and to deal with a unique resource for several, quite different purposes, a data base was developed enabling optimum knowledge management and easy access. The data base covers also legal restraints and is being linked with the institutional publication repository. To identify the lines available detailed information is provided for each line, as the international designation, a short name, the characterization/description, and the genetic modification including the technique used therefore. The origin of the mutation (gene-ID# and donor organism), the origin of regulatory elements and their donors are listed as well as the genetic background, back-cross generation, phenotype, possible publications, keywords, and some in-house information. Also aspects of animal welfare, obligations to record genetically modified organisms, and technology transfer are displayed; the latter to make licenses possible (if legally permitted). Material transfer agreements, patents, or legal restrictions are listed. This data base helps to avoid double-imports, saves animals and costs since a redundant generation or import can be omitted. However, this is a contribution to the 3R principles developed by Russell and Burch.